PARADIGMA SAKSI MAHKOTA DALAM PERSIDANGAN PIDANA DI INDONESIA - Amrullah Amrullah (Jurnal Ilmiah Peuradeun, 2014)
The practice of criminal justice is the running application of the law of criminal procedure in accordance with existing rules in the Code of criminal procedure. However, in practice many things that are not regulated under the Criminal Procedure Code but in practice it continued in use as well as the application of a crown witness. Indicate that the basic consideration of the use of crown witness in the practice of criminal justice is the first; there is no prohibition on the use of crown witnesses in the Criminal Code. Second, the crown witness justified its use in the application Splitsing (split case) is based on the rules of Section 142 Criminal Procedure Code. Application of crown witness has a very important position in criminal case reveals minimal evidence, especially in the case of inclusion. But the crowning issue or an appreciation of the crown witness is often overlooked and is up from the panel of judges, it This is caused by the absence of a rule that says the crown (the award) is how that should be given to the crown witness.